Plasma gelsolin and matrix metalloproteinase-3 levels as diagnostic markers for psoriatic arthritis - Y. A. Zamzam; T. F. Mansour; R. M. Salem; H. A. A. Hanout; R. A. Mostafa (The Ukrainian Biochemical Journal, 2024)
Recent studies have revealed a high prevalence of undiagnosed psoriatic arthritis (PsA) in patients with psoriasis. Diagnosis of psoriatic arthritis has proven challenging because the symptoms of the disease are nonspecific, rheumatoid factor is not detectable, and acute phase reactant levels may be normal. Therefore, identifying soluble biomarkers for diagnosing PsA in psoriasis patients may help in early diagnosis and proper management. The aim of the work was to evaluate plasma gelsolin and matrix metalloproteinase-3 (MMP-3) levels as potential markers for PsA. This case-control study included 25 healthy controls and 50 psoriasis patients, who were divided into 25 patients with psoriasis only and 25 patients with psoriatic arthritis. Plasma levels of gelsolin and MMP-3 were measured using ELISA. It was shown that patients with PsA had significantly lower gelsolin and significantly higher MMP-3 plasma levels compared to patients with psoriasis only. For detecting PsA, gelsolin and MMP-3 had sensitivity of 96% and specificity of 92 and 80% for each, respectively. Gelsolin level negatively while MMP-3 level positively correlated with such parameters as disease activity for psoriatic arthritis, composite psoriatic disease activity index, and inflammatory markers including high-sensitivity C-reactive protein and erythrocyte sedimentation rate. It was concluded that plasma gelsolin and MMP-3 levels could serve as potential biomarkers for diagnosing PsA and monitoring the disease progression in PsA patients.